2014
DOI: 10.1371/journal.pone.0094209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Estrogen Signaling in a Mouse Model of Inflammatory Bowel Disease: A Helicobacter Hepaticus Model

Abstract: The pathogenesis of inflammatory bowel diseases (IBD), Crohn's disease and ulcerative colitis, is due in part to interactions between the immune system, genetics, the environment, and endogenous microbiota. Gonadal sex hormones (GSH), such as estrogen, are thought to be involved in the development of IBD as variations in disease severity occur during pregnancy, menopause, or oral contraceptives use. In certain strains of mice, infection with Helicobacter hepaticus triggers IBD-like mucosal inflammation that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…The positive role of estrogen in maintaining intestinal barrier function may be through maintenance of tight junctions and/or influence on inflammatory response. 102…”
Section: Motility and Permeabilitymentioning
confidence: 99%
“…The positive role of estrogen in maintaining intestinal barrier function may be through maintenance of tight junctions and/or influence on inflammatory response. 102…”
Section: Motility and Permeabilitymentioning
confidence: 99%
“…However, female mice develop a more severe disease when inoculated with H. hepaticus than male mice, which seems to contradict the aforementioned studies. 27 Female mice secrete higher levels of IL-6 and IL-12 than male mice in chronic DSS and TNBS models. Interventions acting on the cytokine signaling system may therefore have a different efficacy in male versus female mice.…”
Section: Discussionmentioning
confidence: 98%
“…25,26 Estrogen-deficient mice infected with the bacteria Helicobacter hepaticus and treated with placebo developed a much more severe inflammation than estrogen-deficient mice treated with 17b-estradiol. 27 Specifically, it is suggested that signaling through the estrogen-b-receptor seems to decrease disease severity. However, female mice develop a more severe disease when inoculated with H. hepaticus than male mice, which seems to contradict the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although estrogen signaling through nuclear estrogen receptors (ERs) is generally considered to promote immunity, correlating with enhanced immune responses against infectious agents in female patients, 19 divergent estrogen effects have been reported in other disease settings. Several genetic and bacterial models of IBD in mice display a similar female bias for severe intestinal inflammation 20, 21 and studies of estrogen signaling in these systems have revealed cell-specific mechanisms of estrogen-mediated immunomodulation. Exogenous estrogen treatment in Th1-linked experimental colitis has been shown to reduce tissue inflammatory and injury indices, and suppress proinflammatory cytokine expression and mast cell protease levels in an ER-dependent manner.…”
Section: Estrogen Signaling and Pregnancy Factors In Ibdmentioning
confidence: 99%
“…22 Helicobacter hepaticus inoculation of ER knockout mice further revealed that functional ERβ signaling in the absence of ERα is sufficient to dampen intestinal inflammation and proinflammatory cytokine expression in bacterially-induced IBD. 20 Estrogen signaling through intestinal epithelial cell ERβ supports tight junction development and decreases intestinal permeability, thereby reinforcing the primary cellular mucosal barrier to omnipresent gut microbes. 23 Furthermore, ERβ mRNA levels are reduced in colonic biopsies from IBD patients and IL-10 knockout (IL-10 −/− ) mice, with increased colonic permeability preceding the onset of colitis in this genetic mouse model.…”
Section: Estrogen Signaling and Pregnancy Factors In Ibdmentioning
confidence: 99%